Perancangan Ruang Terbuka Hijau pada Lahan Tempat Pembuangan Akhir Sampah Pasca Operasi Pasir Impun untuk Membentuk Partisipasi Masyarakat - Esti Galuh Arini (PLANNERS INSIGHT : URBAN AND REGIONAL PLANNING JOURNAL, 2019)
This research is an example of designing City Green Open Space (RTH) by considering community opinion in the process and encouraging the growth of participation from the community itself as the ultimate goal. As a case study, Pasir Impun post-operation landfill (TPA) in Bandung City was taken. With the aim of increasing the area of RTH, in Bandung Strategic Plan 2004-2009, one of the planned programs was to re-arrange the Post-Operation Landfill, Pasir Impun, in the East Bandung. In terms of technical feasibility, Pasir Impun post-operation landfill is considered the most ready to be converted, Whereas from a social standpoint, this landfill is surrounded by fairly dense residential areas (1,254 inhabitants), who do not have public open spaces that can be used by the community for recreation or other social activities, so that the Pasir Impun post-operation landfill with an area of ± 4.1 Ha is considered to have great potential to be developed as an local Green Open Space. It is expected that with this approach, the results of the design of Green Open Space on the Post-Operation Landfill Pasir Impun, can answer the basic needs of the community and in the end can guarantee the success of land conversion and the program sustainability. The design process begins by conducting a survey directly to the land and surrounding settlements, interviews with relevant parties, distributing questionnaires to the community, as well as literature and precedents. Furthermore, an analysis of these activities is carried out to compile and formulate a space program and design criteria as the basis for the design that will be created or developed. The final result of this design process is a design simulation of local open space on the Pasir Impun post-operation landfill.